Different time scales of motion integration for anticipatory smooth pursuit and perceptual adaptation - Maus, Gerrit W. (J Vis, 2015)
When repeatedly exposed to moving stimuli, the oculomotor system elicits anticipatory smooth pursuit (ASP) eye movements, even before the stimulus moves. ASP is affected oppositely to perceptual speed judgments of repetitive moving stimuli: After a sequence of fast stimuli, ASP velocity increases, whereas perceived speed decreases. These two effects—perceptual adaptation and oculomotor priming—could result from adapting a single common internal speed representation that is used for perceptual comparisons and for generating ASP. Here we test this hypothesis by assessing the temporal dependence of both effects on stimulus history. Observers performed speed discriminations on moving random dot stimuli, either while pursuing the movement or maintaining steady fixation. In both cases, responses showed perceptual adaptation: Stimuli preceded by fast speeds were perceived as slower, and vice versa. To evaluate oculomotor priming, we analyzed ASP velocity as a function of average stimulus speed in preceding trials and found strong positive dependencies. Interestingly, maximal priming occurred over short stimulus histories (∼two trials), whereas adaptation was maximal over longer histories (∼15 trials). The temporal dissociation of adaptation and priming suggests different underlying mechanisms. It may be that perceptual adaptation integrates over a relatively long period to robustly calibrate the operating range of the motion system, thereby avoiding interference from transient changes in stimulus speed. On the other hand, the oculomotor system may rapidly prime anticipatory velocity to efficiently match it to that of the pursuit target.